2016
DOI: 10.3311/pptr.8208
|View full text |Cite
|
Sign up to set email alerts
|

Hydroplaning on Sloping Pavements Based on Inertial Measurement Unit (IMU) and 1mm 3D Laser Imaging Data

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…It is speculated that driver behavior changed on rutted roads so this impacted the resulting accident rate. Gallaway (1971), Luo (2015), Guo (2013) considered the impact of the road environment where the rut is located on the water film thickness and hydroplaning speed. Gallaway and FHWA collaborated to study the effects of pavement cross slope, pavement texture, and drainage length and rainfall intensity on the water film thickness through laboratory experiments.…”
Section: Safety Evaluation Of Water-filled Ruttingmentioning
confidence: 99%
“…It is speculated that driver behavior changed on rutted roads so this impacted the resulting accident rate. Gallaway (1971), Luo (2015), Guo (2013) considered the impact of the road environment where the rut is located on the water film thickness and hydroplaning speed. Gallaway and FHWA collaborated to study the effects of pavement cross slope, pavement texture, and drainage length and rainfall intensity on the water film thickness through laboratory experiments.…”
Section: Safety Evaluation Of Water-filled Ruttingmentioning
confidence: 99%
“…In this study, we adopted the Gallaway model [29] and the USF (University of South Florida) model [30] based on Luo's DFT (Dynamic Friction Tester) test results [20], which indicated that the two models provide more accurate results in hydroplaning speed prediction than other models. The Gallaway model is a classic model developed in 1979 by Gallaway B.M.…”
Section: Hydroplaning Risk Evaluationmentioning
confidence: 99%
“…Since the laser point data includes the geometric information, we can estimate the water-film thickness by introducing the analytical models. Using this method, researchers [19,20] proved the feasibility of the 3D surface data for water-film estimation, demonstrating the feasibility of hydroplaning risk evaluation. However, current studies focus mainly on a relatively small region (one single lane) due to the coverage limits of the laser detection system.…”
Section: Introductionmentioning
confidence: 96%
“…Implementing a vehicle using this technique can generate a safer and more maneuverable vehicles for general and military users. Luo et al [11] studied the risk of the water slide on horizontal and vertical slopes and calculate the predicted velocity of water slide using two models that based on Gallaway and USF using three-dimensional laser imaging data and showed that the sliding speed is more sensitive to the lateral slope of the longitudinal slope, decreases with longitudinal grade increase and increases with lateral slope. Mashadi et al [12] designed a gyroscopic system to apply reverse (corrective) torque to the vehicle in the opposite direction of the coup.…”
Section: Introductionmentioning
confidence: 99%
“…safe speed of the vehicle regarding hydroplaning At a horizontal plane where the track angle equal zero, equation of safe speed equal :≥ *(16)Where the track angle equal ( ) could be any value as shown on figure 3 ,then equation of safe speed equal to : safe speed of the vehicle regarding coup, due to gyroscopic moment effect. During navigation on a curved road then active gyroscopic couple would be created, acting on the system due to the rotating parts, and also centrifugal couple has a tendency to overturn the vehicle , therefore , the total overturning couple ( ) is given by: =active gyroscopic couple + centrifugal couple = At a horizontal plane , where the track angle equal zero , then the above equation equal is rewritten as follow [Vehicle travelling on pavement slippery segment with horizontal curve[11]…”
mentioning
confidence: 99%